Marian Kallas, Irena Lipowicz, Zygmunt Niewiadomski, Grażyna Szpor, Prawo administracyjne. Część ustrojowa, 2002 - Maciejewski, Tadeusz (Czasopismo Prawno-Historyczne, 2003)
Recenzja: Marian Kallas, Irena Lipowicz, Zygmunt Niewiadomski, Grażyna Szpor, Prawo administracyjne. Część ustrojowa, Warszawa 2002, ss. 345, Wydawnictwo Prawnicze Lexis Nexis.